1975
DOI: 10.1007/bf01261890
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the transition effect in layered absorbers

Abstract: The problem of radiation protection has become important with the development of high-energy particle accelerators. High-energy particles passing through a shield generate showers in it. There is an indication in the papers [1][2][3][4][5] that dampingofa shower occurs more rapidly in an inhomogeneous medium than in a homogeneous one. In order to design a layered shield, it is necessaryto know the quantitative variations of the shower's characteristics in an inhomogeneous medium.Instruments are employed in hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In the region of negative voltages, the measured dependence of the yield is approximated by a curve of the type (1). The value of the coefficient p 1 indicates the yield of above-barrier electrons, which can also be approximately determined from the data in Fig.…”
Section: Experimental Research Of the Low-energy Component Yield Of T...mentioning
confidence: 99%
See 2 more Smart Citations
“…In the region of negative voltages, the measured dependence of the yield is approximated by a curve of the type (1). The value of the coefficient p 1 indicates the yield of above-barrier electrons, which can also be approximately determined from the data in Fig.…”
Section: Experimental Research Of the Low-energy Component Yield Of T...mentioning
confidence: 99%
“…The value of the coefficient c 1 , represents the total yield of the secondary low-energy emission plus the high-energy background. By subtracting the background value p 3 , see (1), from c 1 , we obtain the value of the total yield of secondary low-energy electron emission, which can also be approximately estimated from the data shown in Fig. 3.…”
Section: Experimental Research Of the Low-energy Component Yield Of T...mentioning
confidence: 99%
See 1 more Smart Citation
“…The length of dechanneling is the parameter which allows one to determine the thickness of the crystal up to which the particles move inside it in the channeling mode. Attempts to determine the dechanneling length of negatively [11] (110) e − 0.855 21.1 [12] (110) e − 0.855 48.0 [13] (110) e − 0.855 9.7 [14] (110) e − 1.2 24.2 [15] (110) π − 150 6.2 [16] (111) e − 23.6 [11] (111) e − 0.855 23.7 [17] (111) e − 0.855 15.9 [14] (111) e − 3.35-14 15.3 [18] (111) e − 0.5-100 27 [19] (111) e − 50 6.6 [20] charged particles have been repeatedly made previously by means of theoretical calculations, numerical simulations and experiments. In [11], on the basis of the comparison of the root mean square angle of multiple scattering with the critical angle of planar channeling, it was found that the dechanneling length is linearly proportional to the energy of the charged particles:…”
Section: Introductionmentioning
confidence: 99%
“…There are several experimental methods which allow determining the value of the dechanneling length in a crystal. These methods are associated with the detection of the yield of the atomic electrons knocked out from the crystals [15], with the measurement of the low-energy channeling radiation or high-energy bremsstrahlung [12] and with the measurement of the deflection angle of the particles after their passage through a bent crystal [16][17][18]. In the present paper we propose a new method of the dechanneling length determination through the analysis of the particle ionization energy loss spectra in crystals.…”
Section: Introductionmentioning
confidence: 99%